Polarization switching characteristics of 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) lead free ferroelectric thin films by pulsed laser deposition - Kolekar, Y. D.; Bhaumik, A.; Shaikh, P. A.; Ramana, C. V.; Ghosh, K. (JOURNAL OF APPLIED PHYSICS, 2014)
We report on the ferroelectricity for morphotropic-phase-boundary lead (Pb) free 0.5BaTi(0.8)Zr(0.2)O(3)-0.5Ba(0.7)Ca(0.3)TiO(3) (0.5BZT-0.5BCT) thin films. Thin films were grown on Pt/Ti/SiO2/Si substrate using pulsed laser deposition. Raman spectroscopic data combined with the X-ray diffraction analyses confirm body centered tetragonal crystallographic structure 0.5BZT-0.5 BCT thin films on Pt/Ti/SiO2/Si. Polarization studies demonstrate that these 0.5BZT-0.5BCT films exhibit a large remnant and saturation polarization of 37 mu C/cm(2) and 40 mu C/cm(2), respectively, with a coercive field of 140 kV/cm. A correlation between polarization dynamics, structural distortion, and phonon vibration is established. The splitting of X-ray diffraction peak of the thin film in the 2 theta range of 44.5 degrees to 46.5 degrees represents high degree of tetragonality. The tetragonality factor calculated by Rietveld analysis was found to be 0.006 and can be a major cause for the increased remnant polarization value. It is established from Raman spectra that the non-centrosymmetricity due to the displacement of Ti/Zr ions from its octahedral position is related to the peak position as well as the broadening of the A(1) (LO) optical phonon mode. This increase of broadness in the thin film causes an increase in the dipole moment of the unit cell and, hence, the net increase in polarization values. (C) 2014 AIP Publishing LLC.

Role of Li+ and Fe3+ in modified ZnO: Structural, vibrational, opto-electronic, mechanical and magnetic properties - Bajpai, G.; Moirangthem, I.; Sarkar, S.; Barman, S. R.; Vinod, C. P.; Bajpai, S.; Riyajuddin, S.; Ghosh, K.; Basaula, D. R.; Khan, M.; Liu, S. -W.; Biring, S.; et al. (Ceramics International, 2019)
When Fe is doped in ZnO, a situation of charge imbalance is created due to the higher charge of Fe3+. A charge balance may be obtained by co-doping Li+0.5Fe3+0.5 combinations. A solid solution of Zn1-x(Fe0.5Li0.5)xO (0 ≤ x ≤ 0.03125) is synthesized with this viewpoint. The crystallites belong to a wurtzite P63mc space group, with lattice parameters a, b and c increasing nominally for x = 0.0156 and thereafter remaining invariant. The size varies in the range ~ 60–142 nm. Interstitials of Li and Zn ions are formed. Along with Fe3+ substitution these defects are reasons for O interstitials. These oxygen interstitials increase the red emission while reduction of oxygen vacancies reduces the green emission. These point defects create structural distortion and strain which can generate Zn vacancies. Bandgap reduces due to shallow defects. Mid-bandgap states due to oxygen interstitials and Fe 3d-O 2p hybridization result in NIR emission. On the other hand the crystal surface deforms due to Li addition which hardens the materials. A weak ferromagnetism appears at very low temperature which is enhanced by Li+ addition. Long range exchange mechanism between Fe3+ ions appears in the samples, mediated by magnetic polarons due to point defects.
Keywords: hardness; NIR emission; Shallow and deep level defects; Weak ferromagnetism; ZnO